Three-dimensional numerical simulation of mixed convective heat transfer in a horizontal rectangular duct utilizing nanofluids - Mohammed, Hussein A. (Trans Tech Publications, 2014)
Predictions are reported for three-dimensional laminar mixed convective heat transfer using nanofluids in a horizontal rectangular duct. Five different types of nanoparticle, Ag, Al2O3, Au, Cu and SiO2 with nanoparticles volume fractions range of 2% to 10% are investigated. In this study, the effects of nanofluids type, nanoparticles volume fraction of nanofluids and the effect of aspect ratio on the thermal fields were examined. Results reveal that the addition of nanoparticles to the base fluid and their volume fraction tend to increase the Nusselt number along the horizontal rectangular duct (i.e., increases the rate of heat transfer). It was also found that the Nusselt number increases as the aspect ratio decreases.